Engines of innovation : the entrepreneurial university in the twenty-first century - Thorp, H. Holden, 1964-; Goldstein, Buck. (Chapel Hill : University of North Carolina Press, 2013)
Thorp and Goldstein make the case for the pivotal role of research universities as agents of societal change. They argue that universities must use their vast intellectual and financial resources to confront global challenges such as climate change, extreme poverty, childhood diseases, and an impending worldwide shortage of clean water. They provide not only an urgent call to action but also a practical guide for our nation's leading institutions to make the most of the opportunities available to be major players in solving the world's biggest problems.
The entrepreneurial opportunity -- Entrepreneurial science -- Enterprise creation -- Social entrepreneurship -- Multidisciplinary centers -- Leadership -- Academic roles -- Culture and structure -- Teaching entrepreneurship -- Accountability -- The new donors and university development -- Conclusion -- Engines revisited : a three-year tune-up.
'With a new preface and chapter by the authors.'
Includes bibliographical references (pages 163-168) and index.
Keywords: Community and college -- United States; Education, Higher -- Aims and objectives -- United States; Business and education -- United States; Entrepreneurship -- United States